Tailoring English Questions for Primary Special Needs Students - Adnyani, Luh Diah Surya; Laksono, Kisyani; Anam, Syafiul (International Journal of Elementary Education, 2023)
In the literature, it is believed that question is an integral part of education. However, the studies on questions used by teachers in all education levels are mainly conducted on typical development students. Studies on how teachers use English questions to enhance communication and learning outcomes of students with special needs are still limited. The aims of this study is to analyze how teachers in a bilingual school expose English as a second language and customize the questions to elementary students with special needs. This study used Stake's instrumental case study method. The data were collected by having observation in the special need classroom twice a week for four months. The subject of this study are two teachers from a bilingual school were observed during lessons and individually interviewed. The data is analyzed and encoded anonymized. Then the code is evaluated to identify potential themes to learn more about the important types and considerations of asking strategies for students with special needs. According to the thematic analysis, these teachers employed questions that prioritized two factors: cognitive-based questions and affective-based questions. The study underlines the implications for classroom practice while expanding the understanding of teaching English to special needs students in a bilingual setting.